Trophic convergence of marine vertebrate communities worldwide - Juan David González-Trujillo; Jorge Assis; Ester Serrão; Mark John Costello; Eliza Fragkopoulou; Manuel Mendoza; Miguel B. Araújo (Proceedings of the National Academy of Sciences, 2025)
Biogeographic regions arise due to constraints on species ranges, fostering lineage divergence as a result. Yet, convergent evolution means that evolutionary distinct lineages can share similar characteristics when subjected to similar environmental conditions. The ecological convergence of distinct regions has been demonstrated in terrestrial communities, but it remains uncertain if marine systems exhibit similar patterns, given the greater ease of dispersal in the ocean. Using information on the dietary preferences of marine vertebrates, we develop an ocean regionalization that groups regions with similar trophic communities, describing how species are organized into trophic guilds and how guilds overlap with one another. Six types of trophic communities emerge globally, largely explained by temperature, productivity, and depth. Regions with analogous environments support similar numbers of species with analogous feeding strategies, even if the species do not share the same evolutionary origins. These findings support the notion that independently evolving sets of marine species can converge into functionally analogous trophic communities when exposed to similar environmental conditions. They also provide a benchmark for studying the functional consequences of global environmental change.